Odpowiedź :
a) 11χ+10=2x+37
11x-2x=37-10
9x=27 /:9
x=3
b)82x-9=-18x+1
82x+18x=1+9
100x=10 /:100
x=0,1
c)-7x+5=11x+41
-7x-11x=41-5
-18x=36 /:(-18)
x=-2
d)45x-19=19x-45
45x-19x=-45+19
26x=-26 /:26
x=-1
11x-2x=37-10
9x=27 /:9
x=3
b)82x-9=-18x+1
82x+18x=1+9
100x=10 /:100
x=0,1
c)-7x+5=11x+41
-7x-11x=41-5
-18x=36 /:(-18)
x=-2
d)45x-19=19x-45
45x-19x=-45+19
26x=-26 /:26
x=-1
11x+10=2x+37
11x-2x=37-10
9x-27/9
x=3
82x-9=-18x+1
82x+18x=1+9
100x=10/100
x=0,1
-7x+5=11x+41
-7x-11x=41-5
-18x=36/-18
x=-2
45x-19=19x-45
45x-19x=-45+19
26x= -26
x=-1
11x-2x=37-10
9x-27/9
x=3
82x-9=-18x+1
82x+18x=1+9
100x=10/100
x=0,1
-7x+5=11x+41
-7x-11x=41-5
-18x=36/-18
x=-2
45x-19=19x-45
45x-19x=-45+19
26x= -26
x=-1
11x+10=2x+37
11x-2x=37-10
9x=27 /9
x=3
82x-9=-18x+1
82x+18x=1+9
100x=10 /100
x=0,1
-7x+5=11x+41
-1x-11x=41-5
-12x=36 /(-12)
x=-3
45x-19=19x-45
45x-19x=-45+19
26x=26 /26
x=1
11x-2x=37-10
9x=27 /9
x=3
82x-9=-18x+1
82x+18x=1+9
100x=10 /100
x=0,1
-7x+5=11x+41
-1x-11x=41-5
-12x=36 /(-12)
x=-3
45x-19=19x-45
45x-19x=-45+19
26x=26 /26
x=1